A relação entre educação em escolas rurais e a permanência dos jovens no campo - (:unkn) unknown (Universidade Federal do Pampa, 2023)
The work has the purpose of highlighting the importance of education for rural people; it addresses the difficulties that students encounter in remaining in rural areas and how education can contribute to stem the exodus of young people. Education in rural schools has been undergoing transformations, whether structural or pedagogical; efforts have been made to use appropriate methodologies, capable of dialoguing with the needs of students and the school community. However, many schools do not go beyond traditional practices and end up teaching far from the situation experienced in the community, causing the reproduction of a tendency to migrate towards the urban area. Subsidies are sought for the constitution of a school focused on valuing the rural space, which promotes the understanding of the context lived by the students and the future expectations in relation to rural development. The Municipal Elementary School Osório Braga in the municipality of Ita-qui-RS is taken on an empirical basis, with data collection carried out with management, teachers and students. It was noticed that the school has a job aimed at keeping young people in the countryside, but its teaching is still urban, so it ends up limiting teachers and coordinators. Within the challenge for changing pedagogical practices, this work can contribute to methodological reflection and the results that have been achieved, enhancing the work developed by UNIPAMPA – Campus de Itaqui with Family Agriculture.
The relationship between education in rural schools and the permanence of young people in the countryside
Keywords: Desenvolvimento rural; Educação rural; Êxodo rural; Jovens rurais; Rural development; Rural education; Rural exodus; Rural youth; CNPQ::CIENCIAS EXATAS E DA TERRA